2019
DOI: 10.1002/jsfa.9935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic acid on recovery yields and characteristics of rohu (Labeo rohita) protein isolates extracted using pH shift processing

Abstract: BACKGROUND Proteins recovery using hydrochloric acid (HCl) in acid‐aided solubilization could cause greater loss in its functionality over alkali‐aided solubilization. Moreover, using HCl in edible foods is also a health concern. Replacing HCl with organic acids for acid‐aided solubilization could address these problems. The aim was to study the effect of organic acid (glacial acetic acid) as a replacement for HCl during pH shift processing on the characteristics and functionality of rohu (Labeo rohita) protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies reported the application of acid-and alkali-based extraction process for extracting proteins from fish, fish waste, and by-products (Baraiya et al, 2020;Nolsφe et al, 2007;Surasani, Tyagi, et al, 2017;Surasani, 2018, Surasani, Mandal, et al, 2018Surasani, Raju, et al, 2019;Surasani, Raju, Shafiq, & Baraiya, 2020).…”
Section: Novelty Impact Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the application of acid-and alkali-based extraction process for extracting proteins from fish, fish waste, and by-products (Baraiya et al, 2020;Nolsφe et al, 2007;Surasani, Tyagi, et al, 2017;Surasani, 2018, Surasani, Mandal, et al, 2018Surasani, Raju, et al, 2019;Surasani, Raju, Shafiq, & Baraiya, 2020).…”
Section: Novelty Impact Statementmentioning
confidence: 99%
“…Several studies reported the application of acid‐ and alkali‐based extraction process for extracting proteins from fish, fish waste, and by‐products (Baraiya et al, 2020; Nolsφe et al, 2007; Surasani, Tyagi, et al, 2017; Surasani, 2018, Surasani, Mandal, et al, 2018; Surasani, Raju, et al, 2019; Surasani, Raju, Shafiq, & Baraiya, 2020). Only a few reports are available on utilization of recovered proteins and by‐products from fish processing waste for human edible purpose (Shaviklo, 2008; Singh et al, 2021; Surasani, 2017; Surasani et al, 2022; Surasani, Raju, Shafiq, Chandra, & Lakshmisha, 2020; Surasani, Raju, & Singh, 2021; Surasani, Raju, Singh, & Joshi, 2021; Surasani, Singh, et al, 2019), which necessitates the further research in this area.…”
Section: Introductionmentioning
confidence: 99%